2010
DOI: 10.1017/s000711450999345x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting metabolisable energy in commercial rat diets: physiological fuel values may be misleading

Abstract: Knowledge about metabolisable energy (ME) intake is crucial for various experimental settings in rodent studies. ME considers faecal and renal energy losses. In particular, faecal energy excretion can vary considerably between differentially composed diets. Thus determination of faecal energy losses, i.e. apparent energy digestibility, is the most important experimental approach to determine ME. Predictive equations for ME such as Atwater factors or an equation for pigs, which are frequently employed for roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…We here use values from the literature referring to Southgate and Durnin who showed that with bomb calorimetry determined and on the other hand calculated values are in good agreement [49]. Another report using a rodent model showed that Atwater factors predicted metabolisable energy with satisfactory accuracy in purified diets as we used here [50]. However, it is of note, that data available for our article was measured in humans or chicken [24], [51].…”
Section: Discussionmentioning
confidence: 99%
“…We here use values from the literature referring to Southgate and Durnin who showed that with bomb calorimetry determined and on the other hand calculated values are in good agreement [49]. Another report using a rodent model showed that Atwater factors predicted metabolisable energy with satisfactory accuracy in purified diets as we used here [50]. However, it is of note, that data available for our article was measured in humans or chicken [24], [51].…”
Section: Discussionmentioning
confidence: 99%
“…gastrointestinal uptake) is similar in all diets. To confirm the Atwater-formula based calculation of ME and assure similar digestibility of macronutrients in each diet, we had previously determined the ME content of each diet experimentally by digestion trials [9]. All diets were fed in a pair-feeding setting, since we explicitly wanted to exclude any effects which could potentially be attributed to differences in energy intake.…”
Section: Methodsmentioning
confidence: 99%
“…However, these potential mechanisms and the effectiveness of low carbohydrate diets have been questioned [8]. Moreover, we have recently shown that the loss of energy via excretion of ketone bodies is quantitatively negligible in rats fed a ketogenic diet and does not contribute substantially to overall energy expenditure [9]. In addition, ketosis was not associated with weight loss in humans [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, this theory has since been widely rejected (4,24). Also, we have previously shown that ketogenic LC-HF diet-induced energy loss via ketone bodies does not quantitatively contribute to the overall energy balance (10). In regard to energy expenditure, two recent investigations have shown that mice fed a ketogenic diet show increased energy expenditure, which could potentially explain LC-HF diet-induced weight loss (25,26).…”
mentioning
confidence: 96%